2014
DOI: 10.1177/0093650214534973
|View full text |Cite
|
Sign up to set email alerts
|

Framing Virtual Experiences

Abstract: In virtual environments (VEs), users experience visceral simulations that feel like the real world. Virtual experiences are proposed as a novel operationalization of gain and loss framed environmental messages. A 2 (gain vs. loss frame) × 2 (high vs. low interactivity) × 3 (pretest, posttest, delayed posttest) experiment was conducted. Immediately following exposure, virtual experiences promoted environmental behavior by reducing paper consumption by 25% compared to a control group. In addition, the gain frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 57 publications
3
58
0
1
Order By: Relevance
“…Experiments 2 and 3 expanded the parallel mediation model to demonstrate the power of accelerating the progression of time during an embodied experience in IVEs. Echoing earlier results (Ahn, 2015;Ahn et al, 2015), the acceleration of time in IVEs rendered the causal relationship concrete by depicting present behavior and future consequences. As a result, individuals were more likely to perceive the environmental risk to be imminent.…”
Section: Theoretical Contributions and Practical Implicationsmentioning
confidence: 86%
“…Experiments 2 and 3 expanded the parallel mediation model to demonstrate the power of accelerating the progression of time during an embodied experience in IVEs. Echoing earlier results (Ahn, 2015;Ahn et al, 2015), the acceleration of time in IVEs rendered the causal relationship concrete by depicting present behavior and future consequences. As a result, individuals were more likely to perceive the environmental risk to be imminent.…”
Section: Theoretical Contributions and Practical Implicationsmentioning
confidence: 86%
“…Despite the differences between virtual interactions and physical interactions, researches successfully use IVEs to answer questions that cannot be easily addressed just using traditional surveys [46], which are the tools that are used most frequently in the research for gathering data on behavior. Research has shown that users act in similar ways within IVEs as they do in physical environments and have similar feelings of presence within such environments [43,[47][48][49]. IVEs allow the users to feel immersed within the virtual space as if they were in a physical space.…”
Section: Methodsmentioning
confidence: 99%
“…A study on energy use by Midden and Ham (2014) found that participants used less energy after receiving negative feedback compared with positive feedback. As opposed to negative appeals, other research suggests that interventions that illustrate the positive consequences of an individual’s behavior may also catalyze proenvironmental behavior (Ahn, Fox, Dale, & Avant, 2014). An alternative intervention could show the positive effects of certain showering behaviors.…”
Section: Discussionmentioning
confidence: 99%